Outcomes of a Pregnancy with Asthma - A Case Report - Astrit M Gashi (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Asthma is a chronic lung disease. The prevalence of asthma in pregnancy is 1-4%. Asthma can have a negative impact on maternal and fetal health. But it depends if treated adequately or not, during pregnancy. A high risk exists that asthma be complicated before and during delivery, but after delivery, it improves very soon. If asthma worsens during pregnancy, the increase in symptoms usually happens during week 24 to week 36 of pregnancy. If asthma was treated effectively during pregnancy, it can have little or no risk for complications. But, if asthma was severe or poorly controlled during pregnancy, can occur more complications, including: nausea and vomiting, vaginal bleeding, premature birth, pre-eclampsia, intrauterine growth restriction (IUGR), low birth weight, fetus with congenital malformations, complicated labor and neonatal hypoglycemia, tachypnea etc. There are many etiologic factors, that could cause asthma, including; allergens, dust mites, animal dander, etc. Then irritants as cigarette smoke, air pollution, and chemicals. Also, sinusitis, rhinitis, some medications as non-steroidal anti-inflammatory drugs (ibuprofen and naproxen), aspirin, beta blockers and others factors, including emotional stress and cold air. In our case, because of asthma the poorly controlled during pregnancy have happened complications as, preterm birth, PPROM, intrauterine growth restriction (IUGR), low birth weight and the need for neonatal intensive care.